Urinary metabolomics analysis reveals the anti-diabetic effect of stachyose in high-fat diet/streptozotocin-induced type 2 diabetic rats. (1st February 2020) - Liang, Li; Liu, Guimei; Yu, Guoyong; Zhang, Fuming; Linhardt, Robert J.; Li, Quanhong
Highlights: Stachyose (ST) showed the potential of anti-diabetic effect in T2DM rats. A urinary metabolomics strategy was developed to study the anti-diabetic effects of ST. Energy metabolism, gut microbiota and inflammation were most affected. Abstract: As a new platform of systems biology, metabolomics provides a powerful approach to discover therapeutic biomarkers and mechanism of metabolic disease. Type 2 diabetes mellitus (T2DM) is a global metabolic disease, thus, a urinary metabolomics profiling was analyzed to study the anti-diabetic effects and mechanism of stachyose (ST) on high-fat diet- and low dose streptozotocinc-induced T2DM rats. The results showed that ST treatment regulated the level of insulin, low-density lipoprotein cholesterol, and triglycerides, which demonstrates improvement in T2DM on ST treatment. Urinary samples from the ST and T2DM group were enrolled in metabolomics study, 21 differential metabolites were identified from urinary metabolomics analysis, indicating that the ST treatment partly exerted the anti-diabetes activity by regulating energy metabolism, gut microbiota changes and inflammation. A metabolomics strategy is both suitable and reliable for exploring the anti-diabetes effects and understanding the mechanisms of ST treatment against T2DM.